HUBUNGAN MINAT BELAJAR DENGAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SMP NEGERI 2 MERANGIN - Jamila Turrahmi; M. Jainuri; Awatif (Pendidikan Matematika | STKIP YM Bangko, 2021)
The purpose of this study was to describe the significant relationship between interest in learning and mathematics learning outcomes of class VIII Students of SMP Negeri 2 Merangin in the academic year 2020/2021. This study uses a quantitative approach with a correlational method, with a sample of 92 people. The sampling technique is total sampling. The instruments are in the from of questionnaire statement items and even semester UAS results documentation. From the results of the spearman rank analysis obtained rcount > rtable or 0,399 > 0,201 for α = 0,05, significant test analysis obtained Zcount > Ztable or 3,800 > 1,960 while the coefficient of determination was 15,92%. So H0 is rejected and H1 is accepted, which means that there is a significant relationship between interest in learning and mathematics learning outcomes of grade VIII students of SMP Negeri 2 Merangin.